Un sous-sol "sous-estimé" par les collectivités territoriales ? État des lieux et perspectives à partir de l’exemple de la géothermie - Benoit Boutaud; Élodie Jeandel (VertigO, 2023)
The question of the role of local and regional authorities in subsoil development has arisen in recent years, despite the fact that the State has long been the main player. Although their prerogatives in the field of energy and the environment have increased, the subsoil suffers from a lack of interest and a certain invisibility on their part, which leads to an underestimation of its potential for the energy transition. The objective of this article is to shed light on the relationship between these actors and this invisible part of our environment, based on a series of interviews and focusing on the case of geothermal energy. The conclusions show that their level of knowledge is generally very low, although various sources of information exist. This is the result of a combination of unfavourable factors, which until now have been largely dominant (technical confusion, projects temporality, competition with other energies, volume of investments, little consideration given to geothermal energy in urban planning documents, ambivalence of media coverage), and of others more favourable (low-carbon solution, non-intermittent renewable source of energy, limited spatial extent, significant potential). However, this situation could change in view of the energy crisis, the concern to increase energy independence, and the search for solutions capable of making a massive contribution to the transition effort.